O primeiro discurso direto do Senhor no Sinai: um estudo literário-teológico de Ex 19,3-7 - Brey, Petterson (2019)
The Lord's first direct discourse at Sinai presents itself to the reader-listener of biblical narratives as a scenic, artistically composed element. His argument connects to the exodal plot under a rhetorical configuration that is literally decisive for access to what is symptomatic in its deeper layers of meaning. The main protagonist of the exodus plot is the only character to whom the narrator lends his voice. This literary strategy, within the scope of the narrative discourse, constitutes the main key-of-reading of the story told. The voice of the Lord - the vehicle of the legal proclamation that transcribes the character of the God of Israel - comes to the ears of his audience to remind them of divine grace. The discursive retro reference, which puts the reputation of the Lord in perspective, emphasizes its saving acts in favor of those wronged by the oppressive system of slavery Egypt. The God who heard the cry of the oppressed - constituted Moses as his mouthpiece before Pharaoh and commanded him to hear the cry of the slaves and to stop violent oppression - now requires, in return, that Israel listen carefully to his voice. If the people obey the covenant terms, it will be constituted as a peculiar property of the Lord, becoming the bearer of his voice before all the peoples of the earth, as a kingdom of priests and a holy nation. The legitimacy, however, of such office is established by exemplary behavior, which refers to the reputation of the liberator of the oppressed. Just as the Lord has legitimated his sovereignty – by distinguishing himself from human kings with their deities – acting on behalf of the vulnerable, Israel's election is justified only in representing the salvific interests of the sovereign over the whole earth